The Impact of Labor Markets on Emergence and Persistence of Regional Asymmetries - Pierre M. Picard; Eric Toulemonde (Institute for the Study of Labor (IZA), 2001)
This paper investigates the impact of labor markets and economies of agglomeration on firms location. We show that the existence of a lower bound on wage (e.g. a minimum wage or a reservation wage) introduces asymmetric location of firms. Moreover, changes in that lower bound or in global product demand may induce irreversible changes in location equilibria. Asymmetries in firms location may thus emerge and persist.
Keywords: J23; R30; 330; Firms location; persistence; wages; Standorttheorie; Agglomerationseffekt; Regionaler Arbeitsmarkt; Arbeitsmarktflexibilisierung; Mindestlohn; Regionale Konzentration; Regionale Disparität; Theorie